PTH-006 Effect of Medication use on Faecal Occult Blood Test Positivity in the NHS Bowel Cancer Screening Programme. (4th June 2013) - Gill, M D; Bramble, M; Rees, C
Abstract : Introduction: Faecal occult blood test (FOBt) positivity is linked with both tumour site and gender. Left sided cancers, and cancers in men are detected in significantly greater proportions by screening. The aim of this study was to evaluate for an association with certain medication use at time of test, with the FOBt result, in patients diagnosed with a colorectal cancer. Methods: Using a regional colorectal cancer dataset (Northern Colorectal Cancer Audit Group) and Bowel Cancer Screening Programme database, all screen detected and interval cancers (diagnosed after a negative faecal occult blood test, before the next screening round) were identified. Diagnosis date was between April 2007 and March 2010. General Practitioners for each patient were asked to complete a proforma detailing use of hormone antagonists, hormone replacement therapy, anticoagulants, aspirin, non-steroidal anti-inflammatory drugs (NSAIDs), and pre cancer diagnosis cholecystectomy. Medication use within two months of performing a FOBt was deemed positive. Chi-squared and logistic regression analyses were used. Results: Of 514 patients, 346 (67.3%) proformas were returned and suitable for analysis. 120 patients analysed were in the interval cancer group, with 226 in the screen detected cancer group. Between screen detected and interval cancers groups, no difference was found in the use of hormone antagonists, hormone replacement therapy, anticoagulants, and aspirin. Rates of cholecystectomy were equivalent. The use of non-aspirin NSAIDs within two months of test was seen in a significantly greater proportion in the screen detected cancer group (10.6% vs. 4.2%, p = 0.039). For the population who used NA-NSAIDs, there was no difference between groups in gender, tumour location, or stage of tumour. Conclusion: The use of NA-NSAIDs around the time of test was associated with a greater rate of positivity of the FOBt. This finding adds to our understanding of factors influencing the positivity of FOB testing, and may be useful in understanding the rates of interval colorectal cancers within the screening programme. Disclosure of Interest: None Declared.